2023
DOI: 10.3389/fphys.2023.1132830
|View full text |Cite
|
Sign up to set email alerts
|

The crosstalk between BAT thermogenesis and skeletal muscle dysfunction

Abstract: Metabolic defects increase the risk of skeletal muscle diseases, and muscle impairment might worsen metabolic disruption, leading to a vicious cycle. Both brown adipose tissue (BAT) and skeletal muscle play important roles in non-shivering thermogenesis to regulate energy homeostasis. BAT regulates body temperature, systemic metabolism, and seretion of batokines that have positive or negative impacts on skeletal muscle. Conversely, muscle can secrete myokines that regulate BAT function. This review explained t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Regarding the difference in the duration of physical activity with and without heart failure, we consider that some kind of hypometabolism or muscle degeneration might be related to the amount of physical activity. Dysfunction of brawn adipose tissue (BAT) has been shown to occur with heart failure [ 36 ], and BAT has been reported to play an important role in metabolism and sarcopenia [ 37 ]. Secondary sarcopenia (disease-related sarcopenia) associated with heart failure [ 38 ] has been shown to result in atrophy of slow twitch muscle [ 39 ]; in contrast, age-related sarcopenia results in atrophy of fast twitch muscle [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the difference in the duration of physical activity with and without heart failure, we consider that some kind of hypometabolism or muscle degeneration might be related to the amount of physical activity. Dysfunction of brawn adipose tissue (BAT) has been shown to occur with heart failure [ 36 ], and BAT has been reported to play an important role in metabolism and sarcopenia [ 37 ]. Secondary sarcopenia (disease-related sarcopenia) associated with heart failure [ 38 ] has been shown to result in atrophy of slow twitch muscle [ 39 ]; in contrast, age-related sarcopenia results in atrophy of fast twitch muscle [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also shows that housing temperature is a determinant factor in the cancer-induced cellular responses in mice, which are especially influenced in BAT. Due to known interactions between BAT and other tissues in both basal and during cancer 29 , we speculate that initial cancer-induced alterations in BAT bioenergetics could signal other tissues, especially SkM (Sup. Fig.…”
Section: Mainmentioning
confidence: 99%
“…MO damages skeletal muscle morphology and the muscle fibre composition of offspring during postnatal life; 2,3 this is important since skeletal muscle is crucial for thermogenesis and energy expenditure. 4 FNDC5 encodes a membrane protein that is cleaved and secreted as irisin, which is a myokine that is synthesised mainly by skeletal muscle in response to exercise and is regulated in both humans and rodents by the peroxisome proliferator-activated receptor-gamma coactivator 1 α (PGC1 α). 5 It has been suggested that irisin in skeletal muscle is capable of increasing energy expenditure via an increase in the expression of genes related to metabolism, such as PGC-1 α, and uncoupling protein 3 (UCP3), among others.…”
Section: Introductionmentioning
confidence: 99%